Developing the Preventing Model of Transnational Crimes in Russia and Indonesia in the Age of Sanctions and Global Economic Instability - Toebagus Galang Windi Pratama; Ruslan Puzikov; Sergey Lantsov; Vadim Ponkratov; Ekaterina Khomenko; Larisa Vatutina; Gustavo Henrique Rodrigues Pessoa (Qubahan Academic Journal)
This study identifies and compares primary transnational crimes in Russia and Indonesia by investigating solutions tailored to each country's challenges. Using a qualitative comparative approach, we conducted expert interviews with 30 professionals from law enforcement, judiciary, and academia across both countries. This study reveals novel insights into the distinct patterns of transnational crime: Russia primarily faces cybercrime, economic offenses, and money laundering, while Indonesia grapples with human trafficking, environmental crimes, and maritime piracy. These findings contribute to a new understanding of geopolitical variations in transnational criminal activities. Additionally, the study emphasizes the importance of adapting to global instability and sanctions and proposes a preventive "Legal, Economic, Technological" model to address these challenges. This research also uncovers previously unexplored challenges in cross-border cooperation and the adaptation of legal frameworks to evolving criminal tactics. In particular, the model addresses gaps in current strategies by incorporating a more comprehensive and holistic approach to prevent transnational crimes, with a focus on diagnosis and strategic planning. Additionally, this study proposes directions for developing a preventive “Legal, Economic, Technological” model and preventing transnational crimes, including diagnosis and strategic planning. The study results are expected to support the understanding of gaps in current strategies and simultaneously reinforce the utilization of a holistic approach in the fight against complex transnational criminal activities in a global context.